Fulfillment of the Right to Special Treatment of Elderly Prisoners at Class II B Takengon State Detention Center - Gunawan, Wawan; Syam, Amir (RESAM Jurnal Hukum, 2024)
The role of correctional institutions is very important in carrying out services and fulfilling the rights of convicts, including in terms of fulfilling the right to special treatment for elderly convicts. The purpose of this research is to find out the fulfillment of the right to special treatment for elderly convicts in terms of safety and health protection at the Class II B State Detention Center in Takengon. This type of research is empirical juridical research using data sources in the form of primary data obtained from the field directly through interviews and secondary data obtained from primary legal materials, secondary legal materials, tertiary legal materials. The method of data collection was carried out by direct interviews with sources and document studies. The method of data analysis was analyzed qualitatively and presented in a descriptive manner, namely explaining, describing, and describing in accordance with the problems that are closely related to this research. II B Takengon, it has been implemented in accordance with the applicable regulations, namely Article 6 paragraph (1) and Article 7 paragraph (1) of the Minister of Law and Human Rights Regulation Number 32 of 2018 concerning Treatment of Elderly Detainees and Convicts.